Anatomy of a Power Elite / The Provincial Governors of Early Modern France - Harding Robert R (Yale University Press, 1978)
Preface, Introduction, From Patrons to Partisans (1515-1605), The Renaissance System of Governors (1515-1560), The Origins of the Governors' Religious Parties (1560-1577), The Failure of Clientage, The Structure of Governors' New Regimes, The Careers and Families of Governors (1515-1650), Beginning Careers and Mariage, Recruitment to Offices: The Making of a Caste, Status, Wealth and Office, Three Types of Family Fortunes, Arranging Marriages and Ending Careers, Conclusion: The Principal ''Pillars'' of the Republic, The Bureaucratic Solution (1560-1650), Social Centralization, The Shaping of the New Provincial Regimes, Conclusion, Notes, Bibliography, Index.